Optical Spatial Filter to Suppress Beam Wander and Spatial Noise Induced by Atmospheric Turbulence in Free-Space Optical Communications. (18th May 2015) - Darusalam, Ucuk; Priambodo, Purnomo Sidi; Rahardjo, Eko Tjipto
Abstract : We propose an optical spatial filter (OSF) method to suppress beam wander and spatial noise effects. Signal from random displacements of the focus spot around the optical axis within the constricted area is collected. This method advantageously suppresses fluctuations in signal intensity. The OSF consists of a pinhole and cone reflector. The pinhole produces Fresnel diffraction on the focus spot. The cone reflector provides directed reflectance onto the pinhole for random focus spot displacements due to beam wander. The calculations of signal power are based on fluctuations of signal intensity that are minimized by the circular aperture function of the pinhole and the cosine of the reflectance angle from the cone reflector. The method is applied to free-space optical communications at a wavelength of 1.55 μ m with an atmospheric chamber to provide optical propagation media. Based on calculations, the beam wander angles that can be received by the OSF are from 14.0° to 28.0°. Moreover, based on experiment, the OSF with a pinhole diameter of 20.0 μ m and cone reflector diameter of 1.5 mm produces signal power of −15.3 dBm. Both calculations and experiment show that the OSF enhances the received signal power in the presence of turbulence.